Mid-Brunhes strengthening of the Indian Ocean Dipole caused increased equatorial East African and decreased Australasian rainfall - Gupta, Anil K.; Sarkar, Sudipta; De, Soma; Clemens, Steven C.; Velu, Angamuthu (Geophysical Research Letters, 2010)
The tropical Indian Ocean is an important component of the largest warm pool, marked by changes in sea surface temperatures and depths of thermocline and mixed layer in its western and eastern extremities leading to the development of a dipole mode - the Indian Ocean Dipole (IOD). A narrow band of westerlies (7 degrees N to 7 degrees S) sweep the equatorial Indian Ocean during the April - May and October - November transitions between the summer - and winter-monsoon seasons. These Indian Ocean equatorial westerlies (IEW) are closely related to the IOD, intensifying the upper ocean Eastward Equatorial current also known as Wyrtki jets. The strength of the IOD/IEW determines the moisture content in East Africa. A major decrease in the strength of the IEW (strengthening or positive mode of the IOD) during the mid-Brunhes epoch (similar to 300-250 Kyr BP) coincides with a wetter equatorial East Africa, a drier Australasia and a stronger Indian summer monsoon, indicating that the IOD/IEW play a significant role in driving climate change in East Africa, Australasia and South Asia. Citation: Gupta, A. K., S. Sarkar, S. De, S. C. Clemens, and A. Velu (2010), Mid-Brunhes strengthening of the Indian Ocean Dipole caused increased equatorial East African and decreased Australasian rainfall, Geophys. Res. Lett., 37, L06706, doi: 10.1029/2009GL042225.
id: 1966; PT: J; UT: WOS:000276025100002